Globalization and the poor periphery before 1950 - Williamson, Jeffrey G., 1935- (Ohlin lectures, 2006)
"In Globalization and the Poor Periphery before 1950 Jeffrey Williamson examines globalization through the lens of both the economist and the historian, analyzing its economic impact on industrially lagging poor countries in the nineteenth and early twentieth centuries. Williamson argues that industrialization in the core countries of northwest Europe and their overseas settlements, combined with a worldwide revolution in transportation, created an antiglobal backlash in the periphery, the poorer countries of eastern and southern Europe, the Middle East, Africa, Asia, and Latin America."--Jacket